(untitled) (Ahkam: Jurnal Hukum Islam, 2014)
Herbert Spencer’s theory of social difference states that society dynamically develops to adjust with environment. In relation to the history of Islamic calendar, the development can be traced back from the varieties of systems in calendar-making. Such varieties were resulted as Moslem societies must adjustment to their new environment. Formerly, the decision of a new month is done by a method named as rukyatul hilal. Then, as with the development of new methods, there come hisab method, kasyaf method, and others. Kata kunci: Sistem Kalender, Teori Deferensiasi Sosial, Herbert Spencer